2011
DOI: 10.1002/sia.3852
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC/nano‐CeO2 on wear resistance and microstructures of Ti3Al/γ‐Ni matrix laser‐cladded composite coating on Ti–6Al–4V alloy

Abstract: The Ti-6Al-4V alloy is an important aviation material, but has a poor resistance to slide wear. Laser cladding of the Al 3 Ti + Ni/ Cr/C + TiB 2 /Al 2 O 3 + SiC/nano-CeO 2 preplaced powders on the Ti-6Al-4V alloy can form the Ti 3 Al/g-Ni matrix composite coating, which improves the wear resistance of the substrate. In this study, the Al 3 Ti + Ni/Cr/C + TiB 2 /Al 2 O 3 + SiC/nano-CeO 2 lasercladded coating was researched by means of X-ray diffraction, scanning electron microscopy, and energy dispersive spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Li et al [103] demonstrated that adding 1.5 percent n-CeO2 to cobalt-based alloy coatings improved wear resistance. Similarly, Li et al [104] reported that Nano CeO2 approximately doubles wear and tear resistance and avoid the growth of shorter crack formation and grooves when laser cladding of Titanium alloy was subjected to dry sliding wear conditions. Figure 12 represents the relation between microhardness with the percentage of Cerium oxide during the different thermal coating process.…”
Section: Solution 2: Surface Coating By Using Rare Earth Elementsmentioning
confidence: 89%
“…Li et al [103] demonstrated that adding 1.5 percent n-CeO2 to cobalt-based alloy coatings improved wear resistance. Similarly, Li et al [104] reported that Nano CeO2 approximately doubles wear and tear resistance and avoid the growth of shorter crack formation and grooves when laser cladding of Titanium alloy was subjected to dry sliding wear conditions. Figure 12 represents the relation between microhardness with the percentage of Cerium oxide during the different thermal coating process.…”
Section: Solution 2: Surface Coating By Using Rare Earth Elementsmentioning
confidence: 89%